Adaptive periodic event-triggered consensus for multi-agent systems subject to input saturation. Issue 4 (2nd April 2016) - Yin, Xiuxia; Yue, Dong; Hu, Songlin
ABSTRACT: This paper investigates the distributed adaptive event-triggered consensus control for a class of nonlinear agents. Each agent is subject to input saturation. Two kinds of distributed event-triggered control scheme are introduced, one is continuous-time-based event-triggered scheme and the other is sampled-data-based event-triggered scheme. Compared with the traditional event-triggered schemes in the existing literatures, the parameters of the event-triggered schemes in this paper are adaptively adjusted by using some event-error-dependent adaptive laws. The problem of simultaneously deriving the controller gain matrix and the event-triggering parameter matrix, and tackling the saturation nonlinearity is cast into standard linear matrix inequalities problem. A convincing simulation example is given to demonstrate the theoretical results.